2022
DOI: 10.32388/t59m2k
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Factors of Pulmonary Embolism in Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease: A retrospective clinical study

Abstract: BACKGROUND: The occurrence of pulmonary thromboembolism (PTE) in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is not rare, which would seriously affect the prognosis and cause high mortality of patients. OBJECTIVE: To investigate the prevalence, risk factors, and clinical characteristics of AECOPD patients with pulmonary embolism (PE) complications in a tertiary care center, aiming to reduce the rate of missed diagnosis of PE in patients with AECOPD. MATERIALS AND METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…32 Peng et al conducted a retrospective study with 6668 patients hospitalized for AECOPD, and reported that the in-hospital mortality was 1.9%. 33 Five other studies with relatively smaller samples reported inhospital mortality rates of 6.0%, 22 7.0%, 34 7.2%, 35 9.7%, 28 and 10.1%, 23 respectively. Therefore, the observed in-hospital mortality rate in our study is in accordance with previous studies.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…32 Peng et al conducted a retrospective study with 6668 patients hospitalized for AECOPD, and reported that the in-hospital mortality was 1.9%. 33 Five other studies with relatively smaller samples reported inhospital mortality rates of 6.0%, 22 7.0%, 34 7.2%, 35 9.7%, 28 and 10.1%, 23 respectively. Therefore, the observed in-hospital mortality rate in our study is in accordance with previous studies.…”
Section: Discussionmentioning
confidence: 95%
“…31 However, the in-hospital mortality rates were slightly lower in China, which ranged from 1.4% to 10.1%. 22,23,28,[32][33][34][35] Pu et al conducted a prospective cohort study with 12831 AECOPD inpatients, and found that the in-hospital mortality rate was 1.4%. 32 Peng et al conducted a retrospective study with 6668 patients hospitalized for AECOPD, and reported that the in-hospital mortality was 1.9%.…”
Section: Discussionmentioning
confidence: 99%